2008
DOI: 10.1364/oe.16.009357
|View full text |Cite
|
Sign up to set email alerts
|

Targeted transfection of stem cells with sub-20 femtosecond laser pulses

Abstract: Multiphoton microscopes have become important tools for non-contact sub-wavelength three-dimensional nanoprocessing of living biological specimens based on multiphoton ionization and plasma formation. Ultrashort laser pulses are required, however, dispersive effects limit the shortest pulse duration achievable at the focal plane. We report on a compact nonlinear laser scanning microscope with sub-20 femtosecond 75 MHz near infrared laser pulses for nanosurgery of human stem cells and two-photon high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 25 publications
1
91
0
Order By: Relevance
“…Usually a Titanium-Sapphire laser at a wavelength of approximately 800 nm and pulse duration of $100 fs is tightly focused on the cellular membrane creating a sub-micron pore that lasts a fraction of a second. The unmatched precision of the treatment has enabled a number of challenging biological experiments such as the transfection of embryonic zebrafish [7] and stem cells [8]. It was also shown that a transcription factor Elk1 mRNA optoinjected into the soma of primary neurons causes a different cellular response to mRNA injected into the dendrites [9].…”
Section: Biophotonicsmentioning
confidence: 99%
“…Usually a Titanium-Sapphire laser at a wavelength of approximately 800 nm and pulse duration of $100 fs is tightly focused on the cellular membrane creating a sub-micron pore that lasts a fraction of a second. The unmatched precision of the treatment has enabled a number of challenging biological experiments such as the transfection of embryonic zebrafish [7] and stem cells [8]. It was also shown that a transcription factor Elk1 mRNA optoinjected into the soma of primary neurons causes a different cellular response to mRNA injected into the dendrites [9].…”
Section: Biophotonicsmentioning
confidence: 99%
“…Recently, there has been considerable interest in the optical transfection of cells using ultrafast pulsed light [15][16][17][18][19][20][21][22][23] because this approach offers selective targeting and higher efficiency and viability (.90% reported in vitro 22 ) than other methods. Furthermore, femtosecond (fs) near-infrared (NIR) laser-based transfection has been shown to be safe, resulting in high efficiency and high survival rates (93%) of optoporated embryos during development 20 , as well as suitable for in vivo gene delivery 24 .…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In the case of stem cells, however, yields of only 25% have been achieved with opto-transfection. 12,13 In opto-transfection, the cell survival is related to phototoxicity. For example, direct DNA photodamage can occur, as reported for various pulse durations, wavelengths, and number of shots.…”
mentioning
confidence: 99%